Bacterial Diversity in Aquatic Ecosystems over the Central Himalayas, Nepal: Progress and Future Perspectives - Adhikari, Namita Paudel; Adhikari, Subash; Paudel, Ganesh (Janapriya Journal of Interdisciplinary Studies, 2019)
Nepal hosts a large area of freshwater aquatic ecosystem including glacier associated system like glacier-fed streams and lakes as well as stream fed lowland lakes. Bacteriological studies are very important in aquatic ecosystems as bacteria are the major participants in biogeochemical cycles and food web structures. This study reviewed available literature in bacteriological studies of aquatic ecosystems in the Central Himalayas, Nepal and revealed that such studies are very limited. Thus, we conclude that future research works need to proceed through the latest molecular methods with high throughput technique using multiple environmental factors in the aquatic ecosystem.